2011
DOI: 10.1371/journal.pone.0021226
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Lowers Methylglyoxal Dependent Protein Glycation and Limits the Complications of Diabetes

Abstract: The elevated glycation of macromolecules by the reactive dicarbonyl and α-oxoaldehyde methylglyoxal (MG) has been associated with diabetes and its complications. We have identified a rare flavone, fisetin, which increases the level and activity of glyoxalase 1, the enzyme required for the removal of MG, as well as the synthesis of its essential co-factor, glutathione. It is shown that fisetin reduces two major complications of diabetes in Akita mice, a model of type 1 diabetes. Although fisetin had no effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 55 publications
(83 reference statements)
1
97
0
Order By: Relevance
“…Gray, and Acacia berlandieri Benth., was shown to possess anti-proliferative activity and display anticarcinogenic potential by inducing apoptosis. 7,[65][66][67] Fisetin inhibited the invasion and migration of cervical cancer cells by dose-dependently supressing the expression and activity of urokinase plasminogen activator and decreased p38 MAPK phosphorylation. Fisetin affected the nuclear translocation of NF-κB and inhibited tTPA (tetradecanoylphorbol-13-acetate)-enhanced migration and invasion.…”
Section: 49mentioning
confidence: 99%
“…Gray, and Acacia berlandieri Benth., was shown to possess anti-proliferative activity and display anticarcinogenic potential by inducing apoptosis. 7,[65][66][67] Fisetin inhibited the invasion and migration of cervical cancer cells by dose-dependently supressing the expression and activity of urokinase plasminogen activator and decreased p38 MAPK phosphorylation. Fisetin affected the nuclear translocation of NF-κB and inhibited tTPA (tetradecanoylphorbol-13-acetate)-enhanced migration and invasion.…”
Section: 49mentioning
confidence: 99%
“…Fisetin is a potent anti-inflammatory, anti-cancer, and anti-oxidant compound (Suh et al 2008;FunakoshiTago et al 2011;Jash and Mondal 2014). Moreover, it has been demonstrated to have a neuroprotective effect and also to limit the complications of type I diabetes (Maher 2009;Maher et al 2011). Based on the molecular structure of this compound, we hypothesized that its biosynthesis should follow the general pathway of flavonol biosynthesis (Figs.…”
Section: Other Activitiesmentioning
confidence: 99%
“…Previous studies have shown that the glyoxalase system is modified in the tissues of streptozotocin-induced diabetic rats [7], and altered blood Glo1 activity is associated with late diabetic complications [8][9][10]. Moreover, it has been shown that enhancement of the glyoxalase pathway along with a decrease in methylglyoxal-dependent protein glycation prevents the development of several indices of late complications in diabetic mice [11]. However, the factors responsible for the variable susceptibility to diabetic complications and the role of the glyoxalase system in the development of vascular complications in diabetes and obesity are not clear.…”
Section: Introductionmentioning
confidence: 99%